Dielectric Properties of Carbons in Blast Furnace Dust (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This study has presented the cavity perturbation theory applied to measurements of the dielectric properties of carbon materials contained in the blast furnace dust (BFD) at single frequency of around 2.5 GHz using a cylindrical microwave cavity at TM010 mode. In addition, the study shows that multimode microwave cavity system at different TM modes can be used to measure the microwave complex permittivity of these materials in the frequency range of 2 to 8 GHz.